2015
DOI: 10.1128/iai.00517-15
|View full text |Cite
|
Sign up to set email alerts
|

Tim-3 Induces Th2-Biased Immunity and Alternative Macrophage Activation during Schistosoma japonicum Infection

Abstract: bT cell immunoglobulin-and mucin-domain-containing molecule 3 (Tim-3) has been regarded as an important regulatory factor in both adaptive and innate immunity. Recently, Tim-3 was reported to be involved in Th2-biased immune responses in mice infected with Schistosoma japonicum, but the exact mechanism behind the involvement of Tim-3 remains unknown. The present study aims to understand the role of Tim-3 in the immune response against S. japonicum infection. Tim-3 expression was determined by flow cytometry, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Throughout the process of wound healing, macrophages play a vital role since they have the ability to phagocytose and clear necrotic tissue, pathogenic microorganisms and foreign matter 19 . They can also secrete various cytokines and chemokines to stimulate cell proliferation and collagen deposition, promoting vascularization and granulation 20 , 21 . There are two different activation patterns of macrophages, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the process of wound healing, macrophages play a vital role since they have the ability to phagocytose and clear necrotic tissue, pathogenic microorganisms and foreign matter 19 . They can also secrete various cytokines and chemokines to stimulate cell proliferation and collagen deposition, promoting vascularization and granulation 20 , 21 . There are two different activation patterns of macrophages, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism might involve the increase in the expression of ARG1, induction of the activity of iNOS, as well as the production of ROS (17,18). It has been reported that SEA could upregulate the expression of ARG1 in isolated CD11b + myeloid cells from S. japonicum-infected mouse spleen in vitro (31). In our study, the level of L-arginine metabolic products (ARG1, NO, and ROS) in spleen MDSCs was compared between normal and S. japonicum-infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…Tim-3 was reported to engage in alternative macrophage activation (Hou et al, 2015 ). Classically activated macrophages (M1 macrophages) participate in phagocytosis, secrete antimicrobial molecules, and activate adaptive immune responses; alternatively activated macrophages (M2 macrophages) participate in the resolution of inflammation after infection (Murray et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real-time PCR was performed to analyse the expression of genes in both human and mouse immune cells. The details of the QRT-PCR assay were previously described (Hou et al, 2015 ). The primers for the genes were derived from the Primer Bank ( https://pga.mgh.harvard.edu/primerbank/ ) and are listed in Supplementary Table 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation